Transporte urbano e insuficiência de acesso a escolas no Brasil - Marcus Saraiva; Luiz Pedro Silva; Carlos Kauê Vieira Braga; Rafael Henrique Moraes Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Providing access to education for low-income populations is essential to reduce inequalities and promote social inclusion. Although the spatial dimension of inequalities in access to education has received attention in recent studies, there is a lack of studies that examine whether children have sufficient access to schools across Brazilian cities and how spatial patterns of accessibility poverty affect the lowest income population. This study presents the first large-scale analysis of accessibility to public schools across the 20 largest cities in Brazil in high spatial resolution. This study focuses on children and teenagers from low-income families and their access to early childhood day-care facilities and secondary schools, which present the lowest levels of school coverage in the country. Considering accessibility by foot and public transport, the study investigates education- -related social exclusion in the intra-urban scale as well as across cities and regions considering multiple thresholds of accessibility poverty. Results indicate that significant actions are still needed to achieve universal access to education in Brazil, particularly in what concerns early childhood and secondary education. We find a substantial portion of poor children with insufficient access to day-care and upper secondary schooling, particularly in low-density areas in the outskirts of cities. The low population density of these areas poses a challenge for the provision of education facilities in enough numbers and spatial coverage to improve school accessibility. The findings of this study contribute to a better understanding of the geographical dimension of poor access to education, which can have long-term effects on social exclusion from opportunities deepening poverty and social inequalities.
10419/284910
Keywords: R4; I2; D6; 330; urban transport; urban accessibility; education; access to schools; social exclusion; transport poverty